Evaluation of metabolic enzymes as predictive biomarkers of risk for prostate cancer progression - Ahmadi, Elham (My University, 2022)
Currently, many patients with early-stage localized prostate cancer (PrCa) (D’Amico: low risk or low-intermediate risk) do not receive immediate therapy but are monitored within systematic AS programs. Prospective trials showed rates of stage reclassification and progression to the treatment of 20–40% over 2–5 years. However, in certain patients, PrCa progresses rapidly to an advanced stage that requires combined modality therapies, which carry increased risk for toxicity and poor outcomes. There is a need to identify biomarkers that can predict the risk for disease progression in this population. Research showed that dysregulation of metabolism is an important hallmark of cancer progression. Here, we pursued a pilot investigation of enzymes of de novo lipogenesis [ATP-citrate lyase (ACLY), Acetyl-CoA Carboxylase (ACC)], lipid oxidation [a-Methylacyl-CoA Racemase (AMACR)], glucose uptake [facilitative glucose transporter 1 (GLUT1)], and folate – glutamate metabolism (PSMA: prostate-specific membrane antigen) as potential biomarkers of PrCa progression in AS patients. With ethics approval from the Hamilton Integrated Research Ethics Board (HiREB), 40 AS patients were accrued prospectively from the Niagara Health System PrCa diagnostic program clinics and were asked to donate their biopsy tissue. 28 patients progressed on repeat biopsies at 12 or 24 months after initial diagnosis and were included in the “Progressed” group, and 12 did not who were included in the “Non-Progressed” group. Baseline diagnostic prostate core biopsy tissues of both groups were evaluated with H&E and immunohistochemistry (IHC) staining for ACLY, ACC, GLUT1, AMACR and PSMA expression (quantified by H-score). H-scores were evaluated in benign and malignant components (epithelial cells) and were compared between the two groups of patients. We observed statistically significant increased GLUT1 expression in malignant epithelial cells of the progressed group compared to the non-progressed group. Also, we found statistically significant increased PSMA expression in the benign epithelial cells of the progressed group compared to the non-progressed group. Further, our results demonstrated a statistically significant increase in ACLY and ACC expression in malignant epithelial cells compared to benign epithelial cells in the progressed group, while AMACR was detected solely in the malignant component. Overall, the results of this pilot study are consistent with the notion of induction of glycolytic metabolism, de novo lipogenesis and increased PSMA expression associated with the risk for PrCa progression. The levels of expression of PSMA within benign epithelial cells and GLUT1 within malignant epithelial cells may have value as predictive markers of risk for PrCa progression in AS patients. Future studies should investigate this concept systematically in larger AS cohorts.
Keywords: Prostate Cancer, Metabolic Enzymes, ACLY, ACC, GLUT1, PSMA, AMACR, Active Surveillance